An X-ray expansion and proper motion study of the Magellanic Cloud Supernova Remnant J0509–6731 with the Chandra X-ray observatory. Issue 2 (8th May 2018) - Roper, Quentin; Filipovic, Miroslav; Allen, Glenn E; Sano, Hidetoshi; Park, Laurence; Pannuti, Thomas G; Sasaki, Manami; Haberl, Frank; Kavanagh, Patrick J; Yamane, Yumiko; Yoshiike, Satoshi; Fujii, Kosuke; et al.
ABSTRACT: Using archival Chandra data consisting of a total of 78.46 ksec over two epochs 7 yr apart, we have measured the expansion of the young (∼400 yr old) Type Ia Large Magellanic Cloud supernova remnant (SNR) J0509–6731. In addition, we use radial brightness profile matching to detect proper-motion expansion of this SNR, and estimate a speed of 7500 ± 1700 km s −1 . This is one of the only proper motion studies of extragalactic SNRs expansion that is able to derive an expansion velocity, and one of only two such studies of an extragalactic SNR to yield positive results in the X-rays. We find that this expansion velocity is consistent with an optical expansion study on this object. In addition, we examine the medium in which the SNR is expanding by examining the CO and neutral H i gas using radio data obtained from Mopra, the Australia Telescope Compact Array, and Parkes radio telescopes. We also briefly compare this result with a recent radio survey, and find that our results predict a radio spectral index α of −0.67 ± 0.07. This value is consistent with high-frequency radio observations of MCSNR J0509–6731.